Evaluation of Seed Germination Parameters of Kalmegh Genotypes in Nursery - Kumar, Jai; Nayak, Hiranmayee; Sinha, Animesh (International Journal of Bio-resource and Stress Management, 2024)
An experiment was conducted during June-July of 2018 and 2019 at Birsa Agricultural University, Ranchi, Jharkhand, India to screen out the most promising genotypes suited for the climatic and edaphic conditions of Jharkhand. Mean number of days taken for completion of seed germination varied from 3.33 days (OAP6) to 13.67 days (JHAP3). Germination period of different Kalmegh genotypes varied from 6.33 days (OAP6) to 15.67 days (JHAP2, JHAP3 and CHAP1). Out of the days taken to complete germination period, nearly 43% of the time was required for seed germination initiation and 62% time to achieve 50% of final germination count. Once the seed started germination, it took 8.82 days to complete seed germination i.e. 57% time was required from initiation to completion of germination. Germination trend of seeds shows that most of the seeds germinated between third to sixth days. Mean germination percentage varied from 21.00% (OAP1) to 97.67% (MPAP3). Altogether eight genotypes namely JHAP1, OAP6, MPAP2, MPAP3, MPAP4, IC111286, IC471890 and GAP1 showed excellent germination percentage having value more than 90.00%. Three Kalmegh genotypes (MPAP3, OAP6, JHAP1) gave highest germination percentage (94.00, 93.00 and 90.67%) respectively. The five genotypes namely; JHAP1, OAP6, MPAP2, MPAP3, and GAP1 were found as most promising genotypes of Kalmegh suited for the climatic and edaphic conditions of Jharkhand.